Secretion of Indoleamine 2,3-Dioxygenase, an Immunomodulatory Substance, by Adipose-Derived Mesenchymal Stem Cell - Laksmitawati, Dian R; Sardjono, Caroline Tan; Pawitan, Jeanne A.; Sadikin, Mohammad; Sandra, Ferry (Indonesian Journal of Cancer Chemoprevention, 2010)
Lipoaspirate, a wasted by product from liposuction procedure recently has been shown to contain abundant adipose-derived-mesenchymal stem cells (MSCs). Mesenchymal stem cells (MSCs) have been studied in many research areas to regenerate many cell lineages. In addition, MSCs have immunomodulatory effect. This capability has been utilized in several clinical studies in hematopoetic stem cell and organ transplantation as a strategy to reduce the risk of Graft versus Host Disease (GvHD). It has been reported that the Ã¢â¬ËstimulatedÃ¢â¬â¢ MSC is able to secrete substances to suppress tissue rejection. One of the substances was known to be indoleamine 2,3-dioxygenase (IDO).ÃÂ  A previous study hasÃÂ  characterized the secretion of IDO by bone marrow-derived MSCs stimulated by an inflammatory mediator interferon gamma (IFN-ÃÂ³). IDO has been detected using Western blot analysis and by High Performance Liquid Chromatography (HPLC) assay. The aim of this study was to detect the presence of IDO in AD-MSCs culture with and without INFÃÂ³ stimulation. Our study showed that AD-MSC stimulated with IFN-ÃÂ³ significantly secreted high level of IDO as detected by Enzyme-Linked Immuno Sorbent Assay (ELISA). Despite its property as a proinflammatory mediator, IFN-ÃÂ³ has shown to be able to induce IDO secretion in MSC culture which suggests the immuno modulatory effect of MSC. This study clearly demonstrates the potential application of adipose-derived MSC in the immunomodulatory strategy for allogenic transplantation.ÃÂ ÃÂ